Pengabdian dalam Pengembangan Personal Hygiene dalam Proses Pengemasan Produk di Desa Ranah Kabupaten Kampar - Ummi Mardhiah Batubara; Alicia Mulya Maharani; Bunga Mulia; Dina Aulia Rifdah; Elly Nur Agustin; Farhan Rio Afdholy; Muhamad Habbil.H; Muhammad Fadhli Alfikri; Melanie Dyas Puteri; Maulina Amiza Yunita; Safira Khairunnisa (LP2M Universitas Muhammadiyah Enrekang, 2022)
This research is to find out the existence of Ranah Village which is one of the traditional villages in Kampar Regency. In the village, of course, there are customary law communities and also customary law that has a strong correlation. The people of Ranah Village still maintain their cultural values ​​and are believed to be in the midst of the civilization that is happening around them. In addition to being rich in customs and culture, in this village there is also a Bumdes that can improve the welfare of the village.